International Intervention and the Rule of Law after Civil War: Evidence from Liberia. (13th March 2019) - Blair, Robert A.
Abstract: What are the effects of international intervention on the rule of law after civil war? Rule of law requires not only that state authorities abide by legal limits on their power, but also that citizens rely on state laws and institutions to adjudicate disputes. Using an original survey and list experiment in Liberia, I show that exposure to the UN Mission in Liberia (UNMIL) increased citizens' reliance on state over nonstate authorities to resolve the most serious incidents of crime and violence, and increased nonstate authorities' reliance on legal over illegal mechanisms of dispute resolution. I use multiple identification strategies to support a causal interpretation of these results, including an instrumental variables strategy that leverages plausibly exogenous variation in the distribution of UNMIL personnel induced by the killing of seven peacekeepers in neighboring Côte d'Ivoire. My results are still detectable two years later, even in communities that report no further exposure to peacekeepers. I also find that exposure to UNMIL did not mitigate and may in fact have exacerbated citizens' perceptions of state corruption and bias in the short term, but that these apparently adverse effects dissipated over time. I conclude by discussing implications of these complex but overall beneficial effects.